The right to social reintegration: a constitutional analysis from the perspective of neuro-law - Carcelén Torres , Luis Javier (2025)
Following the implementation of the Comprehensive Organic Criminal Code (COIP), Ecuadorian criminal law has shifted toward a rights-based model in which punishment is conceived not only as a sanction but also as an instrument for rehabilitation, in accordance with the constitutional principles of human dignity, defense, and due process. The study aims to analyze the right to social reintegration from a constitutional perspective, incorporating the contributions of legal neuroscience as an innovative approach. The research was conducted using a mixed approach. At the qualitative level, deductive, synthetic, and exegetical methods were applied to analyze Ecuadorian legislation, especially Article 201 of the Constitution, and its relationship with neuroscientific postulates. In the quantitative component, a survey was administered to 381 lawyers in private practice in Ecuador, selected from a population of 35,000 professionals, with a confidence  onclusi 95% and a  onclusió error of 5%. The instrument included Likert-type  oncl that measured perceptions of the right to social reintegration, the relevance of neurolaw, and the effectiveness of rehabilitation programs. The results show a critical perception regarding compliance with the right to reintegration (52.5% said it is not guaranteed), but also a high acceptance of neurolaw as an innovative tool (more  on 78% support it to strengthen prison policies). In  onclusión, the study demonstrates that the integration of neurolaw can consolidate a more inclusive, humane, and restorative prison system, which requires a regulatory update that explicitly incorporates its contributions into the Ecuadorian constitutional framework.